1995
DOI: 10.1055/s-0038-1649799
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic Effects of Supraphysiological Levels of Testosterone in Normal Men

Abstract: SummaryThe effects of exogenous testosterone on the haemostatic system were studied in a group of 32 healthy men undergoing a clinical trial of hormonal male contraception. The men received 200 mg testosterone oenanthate (TE) weekly i.m., and plasma samples were taken pretreatment, at defined time points up to 52 weeks of treatment, and 4 and 8 weeks after discontinuing TE. This dose of TE caused a 2-fold increase in trough plasma testosterone levels.TE caused a fall in plasma fibrinogen concentration after 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 12 publications
(17 reference statements)
7
55
2
1
Order By: Relevance
“…Interestingly, oral administration of the androgenic steroid stanozolol has been shown to decrease tPA and PAI-1 antigen levels. 46 This contrasts with the lack of effect of parenteral administration of testosterone esters in males 47 and in females in our present and previous studies. 1,2 This raises the possibility that distinct androgenic compounds have different effects on tPA and PAI-1 levels; alternatively, the route of administration of androgens may be relevant.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, oral administration of the androgenic steroid stanozolol has been shown to decrease tPA and PAI-1 antigen levels. 46 This contrasts with the lack of effect of parenteral administration of testosterone esters in males 47 and in females in our present and previous studies. 1,2 This raises the possibility that distinct androgenic compounds have different effects on tPA and PAI-1 levels; alternatively, the route of administration of androgens may be relevant.…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from fibrinogen, the observed alterations in haemostatic factors returned to pretreatment levels during continued treatment. An increase in both haemoglobin and haematocrit was noticed which was sustained throughout the study period (31). It was concluded that supraphysiological doses of testosterone do not result in a pro-thrombotic state, which is supported by our current study.…”
Section: Discussionsupporting
confidence: 89%
“…In a study of 32 healthy men who received 200 mg testosterone oethanthate by weekly intramuscular injection for 52 weeks in a trial of hormonal male contraception (31), testosterone therapy resulted in a reduction in fibrinogen and PAI-1activity, together with decreases in serum concentrations of the prothrombotic factors protein C and protein S (31). There was no change in the level of tPA, although an increase in antithrombin III activity was observed (31). Apart from fibrinogen, the observed alterations in haemostatic factors returned to pretreatment levels during continued treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with our previous finding that decreased concentrations of testosterone as a result of castration might play an important role in insulin resistance (8,9), an inverse correlation was found, although it did not reach statistical significance, between serum testosterone and fasting serum C-peptide concentrations in men with type 2 diabetes treated without insulin. Testosterone concentration is inversely correlated with procoagulable factors, plasminogen activator inhibitor, and fibrinogen (26). Testosterone has also been shown to act as a vasodilator in both the coronary and systemic circulations in in vitro animal models (27), and short-term intracoronary administration of testosterone, at physiologic concentrations, induces coronary artery dilation and increases coronary blood flow in men with established coronary artery disease (28).…”
Section: Results -mentioning
confidence: 99%